Visual processing speed as a marker of immaturity in lexical but not sublexical dyslexia. (November 2019) - Stefanac, Nicole; Spencer-Smith, Megan; Brosnan, Méadhbh; Vangkilde, Signe; Castles, Anne; Bellgrove, Mark
Abstract: A visual attention span (VAS) deficit has been widely reported in the Developmental Dyslexia (DD) literature, however, consensus regarding what underlies this problem and the nature of its relationship with reading ability remains elusive. Thirty-two children with DD (15 females) were compared with 23 age matched (12 females) and 17 reading matched controls (9 females) on the combined Theory of Visual Attention (CombiTVA) paradigm with traditional letter and novel symbol conditions. The DD group performed more slowly than the age matched controls in terms of processing speed, but similarly to reading matched controls. Moderation analyses revealed that the difference between the DD group and age matched controls was driven by children with equivalent, or relatively poorer, lexical compared with sublexical reading profiles. Results suggest that reduced processing speed indexes reading immaturity, particularly in DD individuals with relative lexical reading deficits, rather than being a unique contributor to reading dysfunction.